Novel insights into non‐HLA alloimmunity in kidney transplantation - Reindl‐Schwaighofer, Roman (Transpl Int, 2019)
Recognition of non‐self structures on donor cells represents the main immunological barrier in solid organ transplantation. The human leukocyte antigens (HLA) are considered the most important non‐self (allo)antigens in transplantation. Long‐term graft attrition is mainly caused by the formation of alloreactive antibodies that are directed against non‐self structures (i.e., epitopes) on cell surface proteins. Recently published data provided evidence for a similar importance of non‐HLA mismatches between donors and recipients in acute rejection as well as long‐term kidney allograft survival. These data suggest a broader concept of immunological non‐self that goes beyond HLA incompatibility and expands the current concept of polymorphic non‐self epitopes on cell surface molecules from HLA to non‐HLA targets. Amino acid substitutions caused by single nucleotide variants in protein‐coding genes or complete loss of gene expression represent the basis for polymorphic residues in both HLA and non‐HLA molecules. To better understand these novel insights in non‐HLA alloimmunity, we will first review basic principles of the alloimmune response with a focus on the HLA epitope concept in donor‐specific antibody formation before discussing key publications on non‐HLA antibodies.